Mild and Direct Access to 7-Substituted-4-trifluoromethylpyrimido[1,2-b]pyridazin-2-one Systems - Petrignet, Julien; Thiery, Emilie; Silpa, Laurence; Abarbri, Mohamed (Synthesis, 2014)
New and efficient methods for the synthesis of 7-substituted-4-trifluoromethylpyrimido[1,2-b]pyridazin-2-one derivatives using either two-step Suzuki/heterocyclization, or two-step heterocyclization/substitution sequences are developed. A variety of substituted products are obtained in good to excellent yields from 3-amino-6-chloropyridazine and ethyl 4,4,4-trifluorobut-2-ynoate.
Keywords: ethyl 4,4,4-trifluorobutynoate; aminopyridazine; heterocyclization; trifluoromethylpyrimido[1,2-b]pyridazin-2-one; Suzuki reaction